PERANCANGAN DESAIN KEMASAN MAKANAN YANG REPRESENTATIF DAN FUNGSIONAL BAGI PENGGUNA - Rachmadita Dwi Pramesti; Resti Dyah Kusumaasri; Maryam Halimah; Sari Rahmawati; Yudha Sujud Pranyoto; Susilawati S Thabrany (Jurnal Poli-Teknologi, 2023)
Packaging design as a food container as well as brand identity, has a big influence on its users. Packaging is designed based on the needs and preferences of the target market or users in order to represent the product and fulfill the functionality of the packaging. Therefore, the purpose of this research is to design a representative packaging design so that it can be used as a food container with features that make it easy for the user and have a good impact on the environment. The research method uses a descriptive qualitative approach with design stages starting from idea preparation to prototype testing. The test results of the structural design and surface design elements of the packaging are analyzed to obtain a final conclusion regarding the suitability and usability of the product and its users. The results of the study show that functional packaging is a box-shaped package so that it can be easily stored when the user cannot finish his food. Besides that, the selection of illustrations for the atmosphere while eating can also represent the type of food and the interactions that occur when eating using the box packaging design.